The Risk-Need-Responsivity Model on Inmate Rehabilitation - Nasiru Zubairu (Journal of Contemporary Sociological Issues, 2023)
The article examines the nature, causes, and implications of inmate rehabilitation in Nigeria by explaining the Risk-Need-Responsivity model. The study reviewed secondary qualitative data, mostly a literature review, and it reinforced and added to the existing body of knowledge on inmate rehabilitation worldwide, particularly in Nigeria. The article finds that there are causes of congestion in the custodial center, such as overuse of imprisonment, a slow judicial process, insufficient prison capacity, a lack of adequate police investigation and prosecution, resource and operational efficiency, and a delay in the administration of justice. The paper adopts Risk-Need-Responsivity (RNR) theory to outline the process of the significance of rehabilitation towards inmates. The model emphasizes assessing and treating inmates according to their ability and risk of re-offending. The research applied a case study that examined the causes of custodial center congestion and identified the implications on inmate rehabilitation in Nigeria. The paper revealed that the consequences of custodial center congestion are spreading infectious disease, breakdown of social control, poor custodial center conditions, access to rehabilitation programs, and too much cost to the State. The study also explained various correctional facilities provide rehabilitation programs based on the criminogenic needs of the inmate, such as counseling programs, adult education, vocational programs, sports and leisure activities, and religious activities. Keywords: Causes, Congestion, Implication, Inmate, Rehabilitation